MANAJEMEN PENGETAHUAN SEBAGAI KEUNGGULAN KINERJA DALAM STRATEGI BERBASIS PENGETAHUAN - Rita Yuanita Toendan (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
In management research to improve the superior performance of organizations such as the Betang Asi Credit Union cooperative in Palangka Raya, the concept of management is the knowledge that applying it can be an advantage in performance. Knowledge management is able to be a competitive strategy with human resources who are able to apply their abilities and expertise in solving problems and exploiting opportunities. Awards support effective learning and motivation to build organizational competence. Based on the results of the study, the organization must be able to help knowledge management to develop strategies to improve employee performance, produce significant results and knowledge, as well as strategies to improve the performance of the Betang Asi CU in Palangka Raya.